1988
DOI: 10.1111/j.1528-1157.1988.tb05800.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, Seizures, and Epilepsy

Abstract: Seizures, epilepsy, and alcohol are complexly interrelated. Although it is commonly perceived that patients with epilepsy experience problems with seizure control if they use alcohol, this is not confirmed by the few experimental studies that have tested the hypothesis. The last 30 years have emphasized the role of withdrawal from alcohol as a mechanism of seizure production. However, this is but one of many potential mechanisms by which seizures and epilepsy may be related to alcohol use and abuse. The rare b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
1
3

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 61 publications
0
33
1
3
Order By: Relevance
“…Die höchste Inzidenz Alkoholentzugs-bedingter Anfälle liegt im höheren Lebensalter [46]. Ältere Patienten sind eher gefährdet, Anfälle durch Medikamentenintoxikation oder durch begleitende Erkrankungen zu bekommen.…”
Section: äTiologieunclassified
“…Die höchste Inzidenz Alkoholentzugs-bedingter Anfälle liegt im höheren Lebensalter [46]. Ältere Patienten sind eher gefährdet, Anfälle durch Medikamentenintoxikation oder durch begleitende Erkrankungen zu bekommen.…”
Section: äTiologieunclassified
“…Individual brains were homogenized for 10 seconds in 2 vol of methanol with an ultrasonic cell disruptor (Sonifer, Branson, Danbury, CT). Homogenates were centrifuged at 10,000g for 10 minutes at 4°C, and supernatants were added to an equal volume of the mobile-phase carrier used for the subsegment assay (10% methanol containing 0.15 M NaCl, 0.15 M NH 4 Cl, and 0.5 g/L sodium EDTA; EICOM, Kyoto, Japan). The mixture was stored at Ϫ80°C for 1 to 3 days until assay.…”
Section: No Metabolites In the Brain And Serummentioning
confidence: 99%
“…As we known, alcohol and epilepsy are complexly interrelated and have been linked since hippocrates 6 . Experimental and clinical studies have been shown that seizures may occur during alcohol intoxication 7,8 and that patients with epilepsy who drink moderate or heavy amounts of alcohol could increase the risk of seizures 6 .…”
mentioning
confidence: 99%
“…Experimental and clinical studies have been shown that seizures may occur during alcohol intoxication 7,8 and that patients with epilepsy who drink moderate or heavy amounts of alcohol could increase the risk of seizures 6 . Moreover, alcohol is a risk factor for ischemic cerebral infarction 9 and increases the chances of head trauma 10 , both of which are known factors in inducing epilepsy.…”
mentioning
confidence: 99%